Clinicopathological patterns of cervical carcinoma in pathological anatomy laboratory at RSUP Sanglah Denpasar, Bali since 2012-2016 - Shameni Subramaniam; I Wayan Juli Sumadi; I.G.A. Sri Mahendra Dewi (DiscoverSys Inc., 2020)
Background: Carcinoma of the cervix is the second most common cancer in women worldwide, Cervical cancer is the most common cancer in women in developing countries. Cervical cancer is the fourth most common cancer in women overall, with an estimated 528,000 new cases in 2012. According to the data clinicopathology of cervical cancer in Bali its still in a small amount.Aims: To obtain information about clinicopathology of cervical carcinoma from the year 2012 – 2016.Methods: A descriptive design study is conducted to determine the clinical pathology profile of cervical carcinoma among patients in Sanglah Hospital, Denpasar, Bali in the year 2012 – 2016. Medical records of the patients were used as the secondary data for this research. This research used the histopathologic document that available in Pathological Anatomy at RSUP Sanglah which mainly reports about patient condition starting from the early anamnesis period until the exact diagnosis of the patient which is due to the laboratory examination or other.Result and Conclusion: As of 2012 to 2016, there were 142 cases of cervical cancer patients in RSUP Sanglah.The age group of 41-50 years has the highest number of patients in the year 2012 – 2016 which is about 52 patients. Abnormal vaginal bleeding is the most common clinical finding of cervical cancer patients from the year 2012- 2016 and carries 53% in 142 cases. It is found out that the most common histopathologic type of cervical cancer from the year 2012 – 2016 is squamous cell followed by adenocarcinoma in the list.